Pengaruh Model Pembelajaran RADEC Berbantuan Media Video Animasi terhadap Peningkatan Kemampuan Berpikir Kritis Matematis Siswa SD - Deviyanti, Anggy; Rahayu, Puji; Mustikaati, Wina (YASIN, 2025)
Mathematical critical thinking ability is an essential competence for elementary school students to face real-world challenges that require problem-solving skills and in-depth analysis. This study aims to analyze the effect of the RADEC (Read, Answer, Discuss, Explain, Create) learning model assisted by animated video media on improving elementary students’ mathematical critical thinking skills. A quantitative quasi-experimental design with a pretest-posttest non-equivalent group was employed. The study was conducted at a public elementary school in Purwakarta Regency, involving two fifth-grade classes: class VC as the experimental group (23 students) and class VA as the control group (23 students). The experimental class used the RADEC model assisted by animated videos, while the control class employed the Discovery Learning model. Results show that the RADEC model assisted by animated video media contributed 22.3% to the improvement of students’ mathematical critical thinking ability. The average score increased from 51.65 to 79.13, with the N-Gain categorized as moderate, whereas the control class showed a low-level improvement. The study concludes that the RADEC model assisted by animated videos is more effective than the Discovery Learning model in enhancing elementary students’ mathematical critical thinking skills.